Anatomy of the wood of Celtis pallida Torrey (Ulmaceae) - Marchiori, José Newton Cardoso (1993)
The wood anatomy of Celtis pallida Torrey (Ulmaceae) is described. The plant is a small woody shrub, native in the United States and from central Argentina to Rio Grande do Sul (Brazil). The anatomical structure is similar with that reported in the literature for Ulmaceae family, the genus Celtis and the species itself, described before upon american samples. The anatomical structure is analysed on a taxonomic and phylogenetic base. A botanical description of the species is also provided due to its rarity in Brazil.